Grotesque architecture; or, rural amusement : consisting of plans, elevations, and sections, for huts, retreats, summer and winter hermitages, terminaries, Chinese, Gothic, and natural grottos, cascades, baths, mosques, moresque pavilions, grotesque and rustic seats, green houses, &c. Many of which may be executed with flints, irregular stones, rude branches, and roots of trees. The whole containing twenty-eight new designs, with scales to each. To which is added, an explanation, with the method of executing them. - Wrighte, William (Salt Lake City, UT : Project Gutenberg, 2022)
"Grotesque architecture; or, rural amusement" by William Wrighte is an architectural publication written in the early 19th century. This book presents a collection of imaginative designs and plans for various types of rustic structures, including huts, hermitages, grottos, and mosques, all aiming to blend into natural landscapes. The author emphasizes the construction of these structures using natural materials, suggesting a harmonization with the rural environment. The content of the book features twenty-eight detailed designs that include plans, elevations, and sections for a diverse range of structures, from traditional rustic seats to elaborate cultural buildings such as mosques and pavilions. Each design is accompanied by specific dimensions and construction techniques, promoting the use of locally sourced materials like flints, irregular stones, and branches. Wrighte's work not only serves as a practical guide for building in a grotesque or rural style but also reflects the aesthetic values of the time, encouraging an appreciation for nature and the creative possibilities of landscape architecture. (This is an automatically generated summary.)
Release date is 2022-11-24
Chris Curnow, David Wilson and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Architecture, Domestic -- Designs and plans